'Hard' and 'soft' aspects of learning as investment: Opening up the neo-liberal view of a programme with 'high' levels of attrition. (1st January 2013) - Bennett, Anna; Hodges, Barry; Kavanagh, Keryl; Fagan, Seamus; Hartley, Jane; Schofield, Neville
For many decades in Australia, enabling educators have worked to engage people in higher education while remaining on the relative periphery of higher education institutions. Recently, there has been an intensification of focus on the value of enabling education from the government policy perspective of widening access for different equity groups, and from the institution, which increasingly operates with a focus on enabling as a source of student capital. Although different, these rationales – both governmental and neo-liberal – tend to consider the education of the student as a form of investment, conceptualised in the form of a productive, manageable citizen or as a potential source of revenue. This environment both enables and constrains enabling educators who work with wider concepts of the value of learning for a diverse range of peoples. Subsequently, enabling educators struggle to fit with dominant discourses that often reduce success to a comparatively narrow definition concerned with completion rates. This issue is important and diverse; however, it is the focus of this paper to outline a recent research project initiated to explore why students do not complete the Open Foundation part-time enabling programme and to obtain information about what they say regarding the challenges they face. It highlights areas of difference from undergraduate programmes and the wider higher education model of attrition, which does not take into account the complex nature of attrition within the enabling sector. The following discussion outlines the scope and findings of this study as a way to build knowledge about aspects of attrition within enabling pathways.